Do politicians gratify core supporters? Evidence from a discretionary grant program - Björn Kauder; Kauder Björn; Potrafke Niklas; Reischmann Markus (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We investigate whether politicians award intergovernmental grants to core supporters. Our new dataset contains information on discretionary project grants from a German state government to municipalities over the period 2008-2011. The results show that discretionary grants were awarded to municipalities with many core supporters of the incumbent state government. Discretionary grants per capita increased by about 1.4 percent when the vote share of the incumbent party in the state election increased by one percentage point. We propose to trim discretionary project grants to the benefit of formula-based grants.
Keywords: D72; H72; H77; 330